Pengaruh Motivasi dan Kepuasan Kerja terhadap Kinerja Karyawan - Cecep Hidayat; Ferdiansyah Ferdiansyah (Bina Nusantara University, 2011)
The purpose of this study was to determine how much influence the work motivation and job satisfaction to employee performance either partially or simultaneously. This type of research is associative with the method of analysis used are simple and multiple regression analysis. Data was collected by distributing questionnaires to all employees of Mutiara Bunda Hospital. The results showed that there are positive and significant influence between motivation and job satisfaction on employee performance